全反式维甲酸调控内质网应激诱导FLT3-ITD蛋白自噬降解促进白血病细胞凋亡 (Zhonghua Xue Ye Xue Za Zhi, 2020)
OBJECTIVE: Endoplasmic reticulum stress（ERS）was used as the research emphasis to further investigate the mechanisms of apoptosis of FLT3-ITD-mutated leukemia cells and decreased expression of FLT3-ITD mutated protein induced by all-trans retinoic acid（ATRA）. METHODS: FLT3-ITD-mutated leukemia cell lines（MV4-11 and MOLM13）were treated with ATRA. Flow cytometry was conducted to assess cell apoptosis. Real-time fluorescent quantitative PCR（RT-qPCR）and Western blot were used to detect the expression of ERS-related and autophagy-related genes and protein, respectively. RESULTS: A low-dose ATRA further increased FLT3-ITD cells and ERS levels. ATRA acted on the ERS-related PERK/eif2ɑ signaling pathway and continued to increase the ERS of FLT3-ITD cells, resulting in an upregulation of apoptotic gene CHOP expression. After the treatment with ATRA, FLT3-ITD protein in FLT3-ITD cells was decreased. Of the two main ERS-related protein degradation pathways, ER-associated degradation（ERAD）and ER-activated autophagy（ERAA）, the expression of ERADrelated protein ATF6 in FLT3-ITD cells was not significantly changed on ATRA, whereas the expression of ERAA-related proteins Atg7 and Atg5 were significantly increased. CONCLUSION: ATRA further raises the ERS level of FLT3-ITD cells continuously by activating the ERS-related PERK/eif2ɑ signal pathway and induces FLT3-ITD protein autophagy degradation through ERAA pathway, which induces apoptosis of FLT3-ITD-mutated leukemia cells. These results provide preliminary evidence on the use of ATRA in the treatment of refractory leukemia with FLT3-ITD.